Comparison of National Surgical Quality Improvement Program Surgical Risk Calculator, Trauma and Injury Severity Score, and American Society of Anesthesiologists Physical Status to predict operative trauma mortality in elderly patients. Issue 3 (March 2022) - Stopenski, Stephen; Kuza, Catherine M.; Luo, Xi; Ogunnaike, Babatunde; Ahmed, M. Iqbal; Melikman, Emily; Moon, Tiffany; Shoultz, Thomas; Feeler, Anne; Dudaryk, Roman; Navas, Jose; Vasileiou, Georgia; et al.
Abstract : BACKGROUND: The Trauma and Injury Severity Score (TRISS) uses anatomical and physiologic variables to predict mortality. Elderly (65 years or older) trauma patients have increased mortality and morbidity for a given TRISS, in part because of functional status and comorbidities. These factors are incorporated into the American Society of Anesthesiologists Physical Status (ASA-PS) and National Surgical Quality Improvement Program Surgical Risk Calculator (NSQIP-SRC). We hypothesized scoring tools using comorbidities and functional status to be superior at predicting mortality, hospital length of stay (LOS), and complications in elderly trauma patients undergoing operation. METHODS: Four level I trauma centers prospectively collected data on elderly trauma patients undergoing surgery within 24 hours of admission. Using logistic regression, five scoring models were compared: ASA-PS, NSQIP-SRC, TRISS, TRISS–ASA-PS, and TRISS–NSQIP-SRC. Brier scores and area under the receiver operator characteristics curve were calculated to compare mortality prediction. Adjusted R 2 and root mean squared error were used to compare LOS and predictive ability for number of complications. RESULTS: From 122 subjects, 9 (7.4%) died, and the average LOS was 12.9 days (range, 1–110 days). National Surgical Quality Improvement Program Surgical Risk Calculator was superior to ASA-PS and TRISS at predicting mortality (area under the receiver operator characteristics curve, 0.978 vs. 0.768 vs. 0.903; p = 0.007). Furthermore, NSQIP-SRC was more accurate predicting LOS ( R 2, 25.9% vs. 13.3% vs. 20.5%) and complications ( R 2, 34.0% vs. 22.6% vs. 29.4%) compared with TRISS and ASA-PS. Adding TRISS to NSQIP-SRC improved predictive ability compared with NSQIP-SRC alone for complications ( R 2, 35.5% vs. 34.0%; p = 0.046). However, adding ASA-PS or TRISS to NSQIP-SRC did not improve the predictive ability for mortality or LOS. CONCLUSION: The NSQIP-SRC, which includes comorbidities and functional status, had superior ability to predict mortality, LOS, and complications compared with TRISS alone in elderly trauma patients undergoing surgery. LEVEL OF EVIDENCE: Prognostic and Epidemiologic; Level III Abstract : A multicenter prospective observational study finds NSQIP-SRC to have superior predicative ability compared to TRISS and ASA-PS when evaluating mortality, length of stay, and complications in elderly operative trauma patients.Supplemental digital content is available in the text.